2008
DOI: 10.1097/01.htr.0000308720.70288.af
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue After Traumatic Brain Injury and Its Impact on Participation and Quality of Life

Abstract: PTBIF has significant impact on well-being and quality of life and cannot be accounted for by comorbid conditions alone, suggesting that it is related to brain injury itself. It appears to be unrelated to demographic and injury variables other than gender. PTBIF does not limit the quantity and frequency of participation. Future research should focus on the relationship between fatigue and the quality of participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
129
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(144 citation statements)
references
References 50 publications
(57 reference statements)
11
129
0
4
Order By: Relevance
“…Individuals with PTBIF tend to report higher levels of disability and lower satisfaction with life than individuals with TBI without fatigue complaints [7,8]. In fact, studies have shown that the presence of PTBIF may prevent return to work [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with PTBIF tend to report higher levels of disability and lower satisfaction with life than individuals with TBI without fatigue complaints [7,8]. In fact, studies have shown that the presence of PTBIF may prevent return to work [9].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the score, the greater the individual's fatigue, with individuals reporting no fatigue were assigned a score of 0. Englander and colleagues [34] used scores of 27 and above as an abnormal amount of fatigue after brain injury, although average fatigue scores for TBI samples have been reported as high as 24.4, SD=11.7, and 28.4, SD=11.3 [8,35]. The current study used GFI scores over 21 to indicate PTBIF based on Cantor et al…”
Section: Measurement Of Fatiguementioning
confidence: 99%
“…42 The presence of fatigue is associated with poorer social integration, decreased levels of productive activities, and decreased overall quality of life. 43 When fatigue persists, it may present a barrier to recovery. Severity of TBI and age have not been found to be predictors of severity of fatigue.…”
Section: Somatic Symptoms Headachementioning
confidence: 99%
“…44 Post-TBI fatigue is most likely the result of a combination of etiologies. Studies have shown that fatigue can be associated with pain, 43 sleep disorders, 45 cognitive deficits, 46 and depression and anxiety. 43 Hypopituitarism, with resultant neuroendocrine abnormalities such as growth hormone deficiency and cortisol deficiency, may also be associated with post-TBI fatigue.…”
Section: Somatic Symptoms Headachementioning
confidence: 99%
See 1 more Smart Citation